Endoscope-Assisted Microneurosurgery for Intracranial Aneurysms - Galzio, Renato J.; Di Cola, Francesco; Raysi Dehcordi, Soheila; Ricci, Alessandro (Frontiers in Neurology, 2013)
Background:The endovascular techniques has widely changed the treatment of intracranial aneurysms.However surgery still represent the best therapeutic option in case of broad-based and complex lesions.The combined use of endoscopic and microsurgical techniques (EAM) may improve surgical results. Objective:The purpose of our study is to evaluate the advantages and limits of EAM for intracranial aneurysms. Methods:Between January 2002 and December 2012,173 patients,harbouring 206 aneurysms were surgically treated in our department with the EAM technique.157 aneurysms were located in the anterior circulation and 49 were in the posterior circulation.Standard tailored approaches,based on skull base surgery principles,were chosen.The use of the endoscope included three steps:initial inspection,true operative time and final inspection.For each procedure,an intraoperative video and an evaluation schedule were prepared,to report surgeons’ opinions about the technique itself.In the first cases,we always used the endoscope during surgical procedures in order to get an adequate surgical training.Afterwards we became aware in selecting cases in which to apply the endoscopy,as we started to become familiar with its advantages and limits. Results:After clipping,all patients were undergone postoperative cerebral angiography.No surgical mortality related to EAM were observed.Complications directly related to endoscopic procedures were rare. Conclusions:Our retrospective study suggests that endoscopic efficacy for aneurysms is only scarcely influenced by the preoperative clinical condition (Hunt-Hess grade),surgical timing,presence of blood in the cisterns (Fisher grade) and/or hydrocephalus.However the most important factors contributing to the efficacy of EAM are determined by the anatomical locations and sizes of the lesions.Furthermore,the advantages are especially evident using dedicated scopes and holders,after an adequate surgical training to increase the learning curve.